Is Mindfulness and Compassion Training Advisable in Alleviating Professional Burnout Among Physicians? Dilemmas and Possibilities in Healthcare System - Boroń Krupińska, Krystyna; Sekułowicz, Małgorzata (Przegląd Badań Edukacyjnych (Educational Studies Review), 2021)
The profession of a physician is a profession of social responsibility, in which medical competence should go hand in hand with non-medical competences. Mental strain, physical fatigue and entanglement in the administrative system can result in chronic stress and contribute to professional burnout, affecting both the well-being of medical staff and the quality of medical care provided. The Author’s intention is to promote mindfulness and compassion training that are considered to be protective and promoting the well-being of physicians resources in conditions of exposure to occupational stress. The analysis was based on 197 documents retrieved from the PubMed/Medline, Science Direct/Scopus databases in years 2008–2017, referring to the impact of mindfulness and compassion training on professional burnout among physicians. Only 21 papers retrieved from the scientific bases met inclusion criteria, referring to the impact of mindfulness and compassion training on professional burnout among physicians. Increasing concentration, improving memory, reducing the level of stress, anxiety and depression and strengthening kindness attitude are the basis for mindfulness and compassion training, which also supports the ability of unreactive responses to difficult situations, develops communication between the physician and the patient.